Preparation method of acetophenone-containing glycidyl ether and DCP (dicumyl peroxide) bi-crosslinked EAA (ethylene acrylic acid) and LDPE (low-density polyethylene) cable material

By introducing diglycidyl ether containing acetophenone structure into the XLPE cable material and carrying out a dual crosslinking reaction, the problem of space charge accumulation in XLPE cable material under high voltage DC electric field is solved, significantly improving the tensile strength and DC breakdown performance of the material, and extending the service life of the cable.

CN119708551AActive Publication Date: 2025-03-28HARBIN UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411557502.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-02
Publication Date
2025-03-28
Estimated Expiration
2044-11-02

AI Technical Summary

Technical Problem

Existing XLPE cable materials are prone to accumulate space charge under the action of high-voltage DC electric field, resulting in distortion of the electric field distribution of cable insulation materials, affecting the electrical resistance and service life of the cable.

Method used

By introducing diglycidyl ether containing acetophenone structure into EAA and LDPE and performing a bicrosslinking reaction with DCP, a bicrosslinking system is formed, and acetophenone structure is quantitatively introduced into the polyolefin polymer chain to avoid migration and phase separation problems.

Benefits of technology

It significantly improves the tensile strength and DC breakdown performance of cable materials, enhances the insulation and electrical resistance of high-voltage DC cable materials, and extends the service life of the cable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005116925090000011
    Figure HDA0005116925090000011
  • Figure HDA0005116925090000012
    Figure HDA0005116925090000012
  • Figure HDA0005116925090000021
    Figure HDA0005116925090000021
Patent Text Reader

Abstract

The invention relates to a preparation method of an acetophenone-containing glycidyl ether and DCP bi-crosslinked EAA and LDPE cable material, and belongs to the technical field of high-voltage direct-current cables. The preparation method of the acetophenone-containing glycidyl ether and DCP bi-crosslinked EAA and LDPE cable material comprises the following steps: taking an ethylene acrylic acid copolymer (EAA) and low-density polyethylene (LDPE) as matrixes, and adopting a micromolecular epoxy compound 5-acetylresorcinol diglycidyl ether and DCP as crosslinking agents; and heating and pressurizing on a plate vulcanizing machine to obtain the double-crosslinking type high-voltage direct-current cable material. The preparation method of the double-crosslinking type high-voltage direct-current cable material is simple, and the breakdown performance and the tensile property of the high-voltage cable material are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a double-crosslinked EAA and LDPE cable material containing glycidyl ether of acetophenone and DCP, and belongs to the technical field of high-voltage direct current cable material preparation. Background Art

[0002] At present, cable materials at home and abroad are composed of low-density polyethylene and various additives such as voltage stabilizers and antioxidants. Among them, the mechanical properties and thermal properties of low-density polyethylene are poor. It is necessary to add free radical crosslinking agent DCP to generate crosslinked low-density polyethylene (XLPE) to enhance its mechanical properties. Under the continuous action of DC high electric field, XLPE will accumulate a large amount of space charge, seriously distort the electric field distribution in the cable insulation material, and directly affect the cable's electrical resistance and service life. Adding appropriate voltage stabilizers to XLPE can effectively suppress space charges. Among them, aromatic ketone compounds are reported to be the most effective voltage stabilizers. Literature reports that the addition of acetophenone can increase the DC breakdown voltage by 30.4% (Jiang Chen et al., Research Progress on Voltage Stabilizers to Suppress Electric Trees in Cable Insulation Materials, Insulation Materials 2018, 51 (7)). Therefore, adding acetophenone derivatives with specific functional groups is a feasible direction to improve the insulation performance of XLPE insulation materials for high-voltage AC and DC cables. However, currently, a long alkyl chain is introduced into the structure of acetophenone or acetophenone is introduced into XLPE by grafting, which may cause problems such as migration, phase separation or inability to quantify the amount of grafting, resulting in the failure of this type of voltage stabilizer to be commercialized.

[0003] The present invention allows EAA and diglycidyl ether containing acetophenone structural units to undergo a cross-linking reaction, so that the structural fragments of acetophenone enter into the EAA molecule in equivalent amounts, and at the same time, a free radical cross-linking agent DCP causes LDPE and EAA to undergo free radical cross-linking, thereby improving the withstand voltage grade of the cable material. This method not only introduces acetophenone into the insulating material quantitatively, but also allows acetophenone and the cross-linking agent diglycidyl ether to directly and quantitatively enter into the polymer chain of polyolefin in a click chemistry manner through a nucleophilic addition reaction, thereby effectively avoiding the problems of migration and phase separation. Summary of the invention

[0004] The invention discloses a method for preparing a double cross-linked EAA and LDPE cable material containing glycidyl ether of acetophenone and DCP, which is characterized in that a certain amount of low-density polyethylene LDPE, small molecule 5-acetylresorcinol diglycidyl ether, ethylene acrylic acid copolymer EAA and dicumyl peroxide DCP are added into a torque rheometer for melt blending to obtain a mixed material; the mixed material is pressed and formed in a flat vulcanizer, and then heated for cross-linking, and a high-voltage DC cable material with significantly improved tensile strength is obtained after cooling.

[0005] Furthermore, the amount of DCP is 2.0% of the mass of LDPE, and the mass of the 5-acetylresorcinol diglycidyl ether / EAA / LDPE blend material comprises: 1.0%-9.0% by mass of EAA, 91%-98% by mass of LDPE, and 0.2%-1.0% by mass of 5-acetylresorcinol diglycidyl ether.

[0006] One of the purposes of the present invention is to provide a method for preparing the composite material, the method comprising the following steps:

[0007] S1, melt blending; blending the DCP / epoxy / EAA / LDPE composite insulation material uniformly to obtain a blended composite material;

[0008] S2, processing and molding; the blended composite material is pressed and molded in a flat vulcanizer, and then cross-linked under pressure, and then placed in a vacuum drying process after cooling to obtain a high-voltage insulating cable material LEAD.

[0009] It is further defined that S1 is specifically as follows: LDPE is added into a torque rheometer, melted at 115°C, the rotation speed is 60r / min, and after mixing for 5 minutes, EAA and the epoxy compound 5-acetylresorcinol diglycidyl ether are added and mixing is continued for 10 minutes, and finally DCP is added and mixed for 3 minutes to obtain a blended composite material.

[0010] It is further defined that the pressing temperature in S2 is 115° C. and the pressure is 15 MPa.

[0011] It is further defined that the pressure cross-linking temperature in S2 is 175° C. and the pressure is 15 MPa.

[0012] It is further defined that the vacuum drying treatment temperature in S2 is 80° C. and the time is 24 h.

[0013] A second object of the present invention is to provide an application of the composite material mentioned above, specifically the composite material is used to make a high voltage DC cable.

[0014] The present invention has the following beneficial effects:

[0015] (1) The present invention designs a small molecule epoxy compound of the acetophenone type, which can undergo a cross-linking reaction with a polymer containing a carboxyl group and is combined with XLPE to construct a double cross-linking system, which significantly improves the mechanical tensile properties of the material.

[0016] (2) The present invention integrates the acetophenone structure that can effectively "capture" electrons into the cable material by cross-linking, and introduces deep electron traps during cross-linking, which significantly enhances the DC breakdown performance of the high-voltage DC cable material.

[0017] (3) The LEAD composite insulating material prepared by the present invention has a simple preparation process, low cost, and easy-to-obtain materials, and has a prospect for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Thermal elongation graphs of LEAD high voltage DC cable materials provided for different embodiments;

[0019] Figure 2 Tensile test result curves of LEAD high voltage DC cable materials provided for different embodiments;

[0020] Figure 3 Weibull distribution diagram of DC breakdown field strength of LEAD high voltage DC cable materials provided for different embodiments,

[0021] Figure 4 Conductivity and current characteristic curves of LEAD high voltage DC cable materials provided for different embodiments; DETAILED DESCRIPTION

[0022] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0023] Embodiment 1:

[0024] The process of preparing the DCP / epoxy / LDPE / EAA modified composite material in this example is as follows:

[0025] Embodiment 1:

[0026] (1) Melt blending: 35 g of LDPE was added into a torque rheometer and melted at 115 °C with a rotation speed of 60 r / min. After mixing for 5 min, 0.7 g of EAA and 0.1 g of epoxy compound 5-acetylresorcinol diglycidyl ether were added and mixing continued for 10 min. Finally, 0.7 g of DCP was added and mixed for 3 min to obtain a blended composite material.

[0027] (2) Processing: The blended composite material was pressed in a flat vulcanizer at a temperature of 115°C and a pressure of 15 MPa, and then pressed for 30 min at a temperature of 175°C and a pressure of 15 MPa to complete crosslinking and obtain LE 1.17 AD 2.0 High voltage DC cable materials.

[0028] Embodiment 2:

[0029] (1) Melt blending: 35 g of LDPE was added into a torque rheometer and melted at 115 °C with a rotation speed of 60 r / min. After mixing for 5 min, 1.4 g of EAA and 0.21 g of the epoxy compound 5-acetylresorcinol diglycidyl ether were added and mixing continued for 10 min. Finally, 0.7 g of DCP was added and mixed for 3 min to obtain a blended composite material.

[0030] (2) Processing: The blended composite material was pressed in a flat vulcanizer at a temperature of 115°C and a pressure of 15 MPa, and then pressed for 30 min at a temperature of 175°C and a pressure of 15 MPa to complete crosslinking and obtain LE 3.82 AD 2.0 High voltage DC cable materials.

[0031] Example 3

[0032] (1) Melt blending: 35 g of LDPE was added into a torque rheometer and melted at 115 °C with a rotation speed of 60 r / min. After mixing for 5 min, 2.1 g of EAA and 0.31 g of the epoxy compound 5-acetylresorcinol diglycidyl ether were added and mixing continued for 10 min. Finally, 0.7 g of DCP was added and mixed for 3 min to obtain a blended composite material.

[0033] (2) Processing: The blended composite material was pressed in a flat vulcanizer at a temperature of 115°C and a pressure of 15 MPa, and then pressed for 30 min at a temperature of 175°C and a pressure of 15 MPa to complete crosslinking and obtain LE 5.61 AD 2.0 High voltage DC cable materials.

[0034] Embodiment 4:

[0035] ((1) Melt blending: 35 g of LDPE was added into a torque rheometer and melted at 115 °C at a rotation speed of 60 r / min. After kneading for 5 min, 2.8 g of EAA and 0.41 g of epoxy compound 5-acetylresorcinol diglycidyl ether were added and kneading continued for 10 min. Finally, 0.7 g of DCP was added and kneaded for 3 min to obtain a blended composite material.

[0036] (2) Processing: The blended composite material was pressed in a flat vulcanizer at a temperature of 115°C and a pressure of 15 MPa, and then pressed for 30 min at a temperature of 175°C and a pressure of 15 MPa to complete crosslinking and obtain LE 8.13 AD 2.0 High voltage DC cable materials.

[0037] The performance tests were performed on the acetophenone-type small molecule epoxy compounds and DCP double cross-linked XLPE high-voltage DC cable materials with different contents prepared in the above Examples 1 to 4, and the specific test results are as follows:

[0038] (1) Prepare dumbbell specimens and measure cross-sectional area according to the test method specified in GB / T 2951.11-2008. Cut the prepared modified high-voltage DC cable material sample into a dumbbell-shaped specimen with a thickness of 1 mm using a cutter. Its total length is 75 mm, and the width of the effective test part is 4 ± 0.2 mm. Its surface is smooth without visible defects, and a marker is used to mark the narrow section with a spacing of 20 mm. The test is carried out in a 200℃ natural ventilation oven. The specimen is suspended from the upper chuck and clamped by the lower chuck. A weight is added to the lower chuck. The weight = 20.4 × specimen thickness × specimen width (including clamps, support rods and weights). The specimen is kept at 200℃ in the oven. After 15 minutes, the distance between the marking lines is measured and the elongation is calculated.

[0039] According to GB / T12527-2008, the thermal elongation of XLPE insulated cables shall not exceed 175%. Figure 1 It can be seen that the cable materials prepared in the present invention meet the standard requirements, and the thermal elongation decreases significantly with the increase of EAA, and the elongation is only 68.5% when the EAA content is 8.13%.

[0040] (2) The above materials were tested by SUNS UTM2203 electronic universal testing machine according to the national standard GB / T528-2009. According to the test method required by the standard, the prepared modified DCP / epoxy / EAA / LDPE composite material sample was cut into a dumbbell-shaped sample with a thickness of 1 mm using a cutter, with a total length of 75 mm and an effective test portion width of 4±0.2 mm. The surface was smooth without visible defects, and a marker pen was used to mark the narrow section with a spacing of 20 mm. The clamp spacing was set to 20 mm, the tensile rate was 250 mm / min, and each material was tested 5 times.

[0041] According to the requirements of standard GB / T22078.1-2008, the tensile strength and elongation at break of XLPE materials for high-voltage power cables should be no less than 12.5MPa and 200% respectively. Figure 2 It can be seen that under the same experimental conditions, the tensile properties of the modified high-voltage DC cable material are significantly improved, with its elongation at break reaching 1343.09% and its tensile strength reaching 26.08 MPa. The elongation at break is 6.71 times higher than the standard, and the tensile strength is 2.08 times higher than the standard.

[0042] (4) The DC breakdown field strength test of the above materials was carried out at 30°C using a cylindrical electrode, with a voltage step-up rate of 1 kV / s and a sample thickness of 50 μm. The sample and the electrode were in transformer oil throughout the entire process, and 10 groups of samples were selected for repeated experiments under each experimental condition.

[0043] The two-parameter Weibull distribution is used to perform statistics on the DC breakdown strength experimental data, which is described as follows:

[0044] P(E)=1-exp(-(E / E b ) β )

[0045] Where: P(E) is the cumulative failure probability, E is the measured breakdown field strength, E b is the characteristic breakdown field strength when the breakdown probability is 63.2%, and β is the shape parameter.

[0046] The Weibull distribution of the DC breakdown strength of the above four materials is as follows: Figure 3 shown.

[0047] Depend on Figure 3 It can be seen that the DC breakdown strength of the four modified high-voltage DC cable materials is improved to varying degrees compared to before modification. After adding epoxy compounds for modification, the breakdown field strength of each content is significantly improved. 3.82 AD 2.0 The breakdown strength reaches a maximum value of 381kV / mm, which is 25.99% higher than that of pure LDPE. The high-voltage DC cable material with this content has good breakdown characteristics.

[0048] (5) According to the electric field strength and temperature of the insulation layer of the high-voltage DC cable during operation, the above four materials are subjected to a conductance current test on 200 μm samples at a field strength of 5 kV to 35 kV within the cable operating temperature range of 30 °C to obtain their EJ curves, as shown in Figure 2. Figure 4 As shown, the polarization time was set to 165 min.

[0049] Depend on Figure 4 It can be seen that the conductivity of the modified high-voltage DC cable material is reduced to 8.26×10 -12 S / m, which indicates that the introduced traps suppress the free movement of charges, which improves the electrical insulation of the HVDC cable material.

[0050] The above description is only a preferred embodiment of the present invention. In view of the fact that technicians in the field of the present invention can make appropriate changes and modifications to the above implementation, the present invention is not limited to the specific implementation described above. Some modifications and changes to the present invention should also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a double cross-linked EAA and LDPE cable material containing glycidyl ether of acetophenone and DCP, characterized in that A certain amount of low-density polyethylene (LDPE), diglycidyl ether containing acetophenone structural units, ethylene acrylic acid copolymer (EAA) and dicumyl peroxide (DCP) are added into a torque rheometer for melt blending to obtain a mixed material; the mixed material is pressed and formed in a flat vulcanizer, then heated and cross-linked, and after cooling, a high-voltage DC cable material with significantly improved breakdown strength and tensile strength is obtained.

2. The method for preparing a double cross-linked EAA and LDPE cable material containing glycidyl ether of acetophenone and DCP according to claim 1, characterized in that The diglycidyl ether containing acetophenone structural unit is 5-acetylresorcinol diglycidyl ether.

3. The method for preparing a double cross-linked EAA and LDPE cable material containing glycidyl ether of acetophenone and DCP according to claim 1, characterized in that The components of the double cross-linking agent are 5-acetylresorcinol diglycidyl ether and dicumyl peroxide DCP.

4. The method for preparing a double cross-linked EAA and LDPE cable material containing glycidyl ether of acetophenone and DCP according to claim 1, characterized in that LDPE accounts for 91%-98% of the mass of the blended material of glycidyl ether, EAA and LDPE.

5. The method for preparing a double cross-linked EAA and LDPE cable material containing glycidyl ether of acetophenone and DCP according to claim 1, characterized in that EAA accounts for 1.0%-9.0% of the mass of the blended material of glycidyl ether, EAA and LDPE.

6. The method for preparing the double cross-linked EAA and LDPE cable material containing glycidyl ether of acetophenone and DCP according to claim 1, characterized in that The content of DCP is 2.0% by mass of LDPE.

7. The method for preparing a double cross-linked EAA and LDPE cable material containing glycidyl ether of acetophenone and DCP according to claim 1, characterized in that The 5-acetylresorcinol diglycidyl ether accounts for 0.2%-1.0% of the mass of the blended material of glycidyl ether, EAA and LDPE.

8. The method for preparing a double cross-linked EAA and LDPE cable material containing glycidyl ether of acetophenone and DCP according to claim 1, characterized in that Mainly used in high voltage DC cable materials.

9. The use according to claim 7, characterized in that The prepared high-voltage DC cable material has a thermal elongation of only 68.5%, a stretching ratio of 1058.21%-1343.09%, and a DC breakdown strength of 381 kV / mm.

Citation Information

Patent Citations

  • Preparation method of cross linked polyethylene insulated material for inhibiting space charge

    CN109776910A

  • Bio-based epoxy resin based on paeonol as well as preparation method and application of bio-based epoxy resin

    CN115449054A

  • Preparation and application of epoxy cross-linked LLDPE / EAA composite insulating material

    CN117362693A

  • Multifunctional deoxybenzoin-based monomers and resins having reduced flammability

    US20140357829A1